Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1212/wnl.0000000000002118
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and cognitive outcomes for clinical trials in children with neurofibromatosis type 1

Abstract: Children with NF1 show distinct deficits in multiple domains. Many outcome measures showed weak test-retest correlations over the 1-year trial period. Cognitive and behavioral outcomes are complementary. This analysis demonstrates the need to include reliable outcome measures on a variety of cognitive and behavioral domains in clinical trials for NF1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 33 publications
2
27
1
Order By: Relevance
“…In addition, MEK inhibitors rescued the plasticity phenotype of CS mice but failed to rescue the cognitive deficits. A review of treatment trials [van der Vaart et al, 2016] in genetic cognitive disorders has shown very limited efficacy, and there is need for larger scale studies, international collaboration and improved reporting and design, particularly with predefinition of outcome measures.…”
Section: Proceedingsmentioning
confidence: 99%
“…In addition, MEK inhibitors rescued the plasticity phenotype of CS mice but failed to rescue the cognitive deficits. A review of treatment trials [van der Vaart et al, 2016] in genetic cognitive disorders has shown very limited efficacy, and there is need for larger scale studies, international collaboration and improved reporting and design, particularly with predefinition of outcome measures.…”
Section: Proceedingsmentioning
confidence: 99%
“…Notably, correlated abnormal behaviors are rescued by treatment with statins ( Li et al, 2005 ) and dopamine re-uptake inhibitors ( Brown et al, 2010 ), respectively. Nevertheless, mixed results in clinical studies ( Bearden et al, 2016 ; van der Vaart et al, 2013 , 2016 ), along with possible memory-associated side effects ( Strom et al, 2015 ), have precluded definitive recommendation of the use of statins in NF1 patients. Therefore, better understanding of molecular mechanisms underlying NF1 neurological issues is crucial to establish successful treatment regimens.…”
Section: Introductionmentioning
confidence: 99%
“…Diffusion tensor imaging (DTI) has been used to examine white matter microstructure in NF1. Fractional anisotropy (FA) is higher in heavily myelinated fiber tracts than in other brain regions (Feldman et al, 2010), and is reduced in NF1 children compared to typically developing children; 60-70% of NF1 children exhibit abnormalities in white matter, including reduced FA (Aydin et al, 2016;Brown et al, 2010;Karlsgodt et al, 2012;Koini et al, 2017;Nemmi et al, 2019;van der Vaart et al, 2016). All these changes lack treatment.…”
Section: Introductionmentioning
confidence: 99%